(untitled) (Universal International Scientific Journal, 2026)
Urbanization is accelerating in Uzbekistan, which is causing unfavorable ecological consequences. The article shows that the shortcomings of urbanization create the need to develop ecological culture, analyzes the role of values ​​in this process with examples. The role of values ​​in the formation of ecological consciousness is emphasized.